Biomechanical Efficacy of Tape Cerclage as an Augment or Stand-alone for Coracoclavicular Ligament Reconstruction. Issue 1 (January 2023) - Wellington, Ian J.; Hawthorne, Benjamin C.; Ford, Brian; Dorsey, Caitlin G.; Quindlen, Kevin J.; Propp, Bennett E.; Obopilwe, Elifho; Cagle, Paul J.; Mazzocca, Augustus D.
Background: Loss of initial reduction of the acromioclavicular joint after coracoclavicular (CC) ligament reconstruction remains a challenge for various repair techniques. Previous studies using polydioxanone suture cerclage augments for CC ligament reconstruction demonstrated poor clinical and biomechanical outcomes. Tape-style sutures have recently gained popularity because of their added stiffness and strength relative to traditional sutures. These tape cerclage systems have yet to be biomechanically studied in CC ligament reconstruction. Purpose: To determine the efficacy of a tape cerclage system as an augment to CC ligament reconstruction. Study Design: Controlled laboratory study. Methods: A total of 24 human cadaveric shoulders were utilized. These were divided into 4 repair groups: anatomic CC ligament reconstruction (ACCR), ACCR with a tape cerclage augment (ACCR + C), tendon graft sling with a cerclage augment (TGS + C), or tape cerclage sling alone (CS). The repairs underwent superior/inferior cyclic loading to evaluate for displacement. Specimens were visually inspected for cortical erosion by the tape cerclage after cyclic loading. Finally, the constructs underwent superior plane load-to-failure testing. Results: Less displacement after cyclic loading was observed in the ACCR + C (mean ± SD, 0.42 ± 0.32 mm), TGS + C (0.92 ± 0.42 mm), and CS (0.93 ± 0.39 mm) groups as compared with the ACCR group (4.42 ± 3.40 mm; P = .002). ACCR + C (813.3 ± 257.5 N), TGS + C (558.0 ± 120.7 N), and CS (759.5 ± 173.7 N) demonstrated significantly greater load at failure relative to ACCR (329.2 ± 118.2 N) ( P < .001). ACCR + C (60.88 ± 17.3 N/mm), TGS + C (44.97 ± 9.15 N/mm), and CS (54.52 ± 14.24 N/mm) conferred greater stiffness than ACCR (27.43 ± 6.94 N/mm) ( P = .001). No cortical erosion was demonstrated in any specimen after cyclic loading. Conclusion: In a cadaveric model at time zero, repairs utilizing a tape cerclage system confer significantly greater load to failure and stiffness, as well as decreased displacement with cyclic loading, when compared with traditional ACCR repair. Clinical Relevance: Tape cerclage augmentation may provide a useful augment for CC ligament reconstruction.